Students’ Perception on The Use of TED Talks to Improve Listening Skills - Wulandari, Annisa Septi; Nur’aini, Siti; Hawa, Faiza (Berumpun: International Journal of Social, Politics, and Humanities, 2024)
Enhancing listening skills is crucial for junior high school students learning English. Innovative teaching tools such as TED Talks offer an interactive platform that might aid this educational goal. This research aims to evaluate the effect of TED Talks on developing listening skills among junior high school learners. The study employed a mixed-methods design involving 34 junior high school students. Participants underwent pre-and post-test assessments to measure their listening skills. Additionally, interviews were conducted to delve deeper into the students' experiences and perspectives regarding using TED Talks in their learning process. The findings revealed that TED Talks significantly enhanced students' English listening skills. After engaging with TED Talks videos, students showed notable improvements in vocabulary acquisition, pronunciation accuracy, and listening comprehension. The high-quality audio and diverse content of TED Talks were credited for these improvements. Furthermore, interviews provided insights into the positive impact of TED Talks on student motivation and engagement, with students expressing increased satisfaction and perceived efficacy in the classroom. TED Talks also contributed to the acquisition of advanced vocabulary and sharpened students' critical thinking skills through exposure to various topics.